2019
DOI: 10.1002/pbc.27968
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical abnormalities related to dexamethasone exposure in survivors of childhood acute lymphoblastic leukemia

Abstract: Survivors of childhood acute lymphoblastic leukemia (ALL) treated with chemotherapy only are at risk for neurocognitive impairment. Regions of interest were identified a priori based on glucocorticoid receptor distribution, and sex‐stratified multivariable linear regression models were used to test associations between brain MRI morphology and total number of intrathecal injections, and serum concentration of dexamethasone and methotrexate. Compared with controls, ALL survivors have persistently smaller volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…These studies should include measures of short- and long-term memory in addition to the measures of working memory included in this study. 13 Neuroimaging studies should include resting-state fMRI with complete coverage of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies should include measures of short- and long-term memory in addition to the measures of working memory included in this study. 13 Neuroimaging studies should include resting-state fMRI with complete coverage of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…12 The hippocampus and cerebellum have the highest concentrations of glucocorticoid receptors. We have previously demonstrated 13 that survivors of childhood ALL treated on chemotherapy-only protocols had smaller Downloaded From: https://jamanetwork.com/ on 12/01/2020 hippocampal, cerebellar, anterior cingulate, precuneus, and dorsolateral prefrontal cortex (DLPFC) regions compared with age-matched healthy individuals in control groups. This finding is consistent with studies that showed that glucocorticoid exposure is associated with smaller brain structures and attenuated functional activity in populations without cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxic agents, radiotherapy or hypoxia (Decker et al, 2017;Lv et al, 2018;Ørbo et al, 2018;Stamenova et al, 2018;Phillips et al, 2020), alcoholism (Lee et al, 2016;Mole et al, 2016;Zahr et al, 2019), alcohol withdrawal (Kühn et al, 2014), familial risk for alcohol use disorder (adolescents) (Maksimovskiy et al, 2019), cannabis use (Beale et al, 2018), cigarette smoking (Durazzo et al, 2013), preterm birth in school-aged children (Aanes et al, 2019) Stress response…”
Section: Neurotoxicitymentioning
confidence: 99%